Armed conflict and schooling: evidence from the 1994 Rwandan genocide - Richard Akresh; Damien de Walque (Institute for the Study of Labor (IZA), 2008)
To examine the impact of Rwandas 1994 genocide on childrens schooling, the authors combine two cross-sectional household surveys collected before and after the genocide. The identification strategy uses pre-war data to control for an age groups baseline schooling and exploits variation across provinces in the intensity of killings and which childrens cohorts were school-aged when exposed to the war. The findings show a strong negative impact of the genocide on schooling, with exposed children completing one-half year less education representing an 18.3 percent decline. The effect is robust to including control variables, alternative sources for genocide intensity, and an instrumental variables strategy.
urn:nbn:de:101:1-20080605111
Keywords: I20; 330; Civil war; human capital investment; education; genocide; Africa; Politischer Konflikt; Bildungsverhalten; Schule; Ruanda